Pemasaran Berbasis Konten dan Emosi: Studi Kasus Kampanye Digital Boneka Bubu - Aditya Putra Wardanu; Ahmad Gozi; Sudarmiatin Sudarmiatin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study is a study of digital marketing strategies related to Boneka Bubu, a product that went viral on social media such as TikTok and Instagram. In this context, emotional and content-based marketing work that connects brands with audiences, especially millennial and Gen Z consumers, plays a very positive role. Humorous approaches, memorable characters, and communities play a role in driving the success of Boneka Bubu's digital campaign which aims to increase brand awareness, sales, and customer loyalty. This analysis examines and tries to solve various issues related to UGC, influencer collaboration, and limited edition promotional strategies that build urgency. Data and research show that emotional-based marketing, which involves consumers in the content creation process, strengthens relationships that lead to conversion and engagement. This study explains the impact of the creative process and authenticity that are emphasized for digital marketing strategies in the age of social media.